Massive Transcranial Parotid Pleomorphic Adenoma: Recurrence after 30 Years - Strub, Graham M.; Georgolios, Alexandros; Graham, Robert S.; Powers, Celeste N.; Coelho, Daniel H. (Journal of Neurological Surgery Reports, 2012)
Pleomorphic adenoma, also known as benign mixed tumor, is the most common tumor affecting the parotid gland and can reach massive size; however, intracranial invasion is rare. Recurrence of pleomorphic adenoma after excision is a well-known phenomenon and can present decades after resection of the primary tumor. Here we present the case of a 53-year-old man who presented to our clinic with ear fullness, otalgia, and hearing loss 30 years after undergoing total parotidectomy and external beam radiotherapy for pleomorphic adenoma. Magnetic resonance imaging revealed a massive transcranial tumor invading the mastoid cavity, the dura of the posterior fossa, the fallopian and semicircular canals, the jugular foramen, the lateral infratemporal fossa skull base, the sigmoid and transverse sinuses, and the superior parapharyngeal region. Gross examination and histopathological studies confirmed that the mass was a recurrent pleomorphic adenoma. Here we discuss the features of recurrent pleomorphic adenoma and review the current literature.
Keywords: pleomorphic adenoma; benign mixed tumor; recurrent pleomorphic adenoma; carcinoma ex pleomorphic adenoma; intracranial invasion